Development and course of arterial hypertension based on 24-hour monitoring of arterial pressure in a population of the Tyumen region - Gapon, L I; Shurkevich, N P; Tonkonog, I M; Sereda, T V; Gubin, D G (Klinicheskaia meditsina, 2004)
Arterial pressure (AP) was monitored in 46 patients with arterial hypertension (AH) aged 18-50 years and in 33 healthy subjects living in Russian North (Tyumen Ob area, Nyagan). The comparison group consisted of 55 patients with AH and 33 healthy subjects living in a moderate climatic zone (Tyumen). The groups were comparable by gender, age, duration of AH, office systolic and diastolic AP (SAP and DAP). Healthy subjects of Tyumen North compared to those living in the moderate climate had more pronounced vegetative imbalance which may transform into AH. The North AH is characterized by high meteorability, impaired circadian AH profile with reduction of the SAP fall day-night and an increase of the DAP fall, greater variability of AP, elevated AP day load, low night DAP. This classifies AH in the northerners as isolated systolic. While AH development in the North takes place due to marked AP fluctuations, in moderate climate it follows a classic variant--due to a DAP rise. The above changes may help prognosis of emergence of cardiovascular complications in hypertensive patients living in the North.